2023
DOI: 10.4317/jced.59225
|View full text |Cite
|
Sign up to set email alerts
|

Lingual Osseous Choristoma: Case report and literature review of this rare entity

Abstract: Intraoral osseous choristoma represents a benign lesion of growing ectopic bone in the soft tissues of the oral cavity. It is considered as rare entity while fewer than 100 cases have ever been reported worldwide. Nevertheless, the pathogenetic mechanism that drives this abnormal ossification still remains controversial. In the present study a case of lingual osseous choristoma in a 50-year old male is presented. The patient was treated with surgical excision and no recurrence was observed. In addition epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The treatment of choice is a surgical excision under local or general anesthesia depending on clinical judgement, considering tumor localization and patient age. There are two reported recurrences for osseous choristoma, one of a buccal soft tissue presented by Long (1991) and another one of the masseter muscle described by Dalkiz (2001) [8,7,11] . Until now, there is no reported recurrence or malignant transformation for lingual osseous choristoma.…”
Section: Discussionmentioning
confidence: 98%
“…The treatment of choice is a surgical excision under local or general anesthesia depending on clinical judgement, considering tumor localization and patient age. There are two reported recurrences for osseous choristoma, one of a buccal soft tissue presented by Long (1991) and another one of the masseter muscle described by Dalkiz (2001) [8,7,11] . Until now, there is no reported recurrence or malignant transformation for lingual osseous choristoma.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have been conducted to unravel the etiology of osseous choristomas. Previous research suggested a congenital basis for these lesions 25,30 . The tongue is formed by the fusion of two parts: the anterior two‐thirds of the tongue is derived from the first branchial arch, while the posterior third is from the third branchial arch.…”
Section: Discussionmentioning
confidence: 99%
“…The developmental theory posits that oral choristoma arises from the entrapment of branchial arches I, II, and III derivatives in the facial region. As most lesions are located at the midline, this explanation appears plausible 30 . However, this theory falls short of providing a complete understanding of the full range of lingual or other intraoral osseous choristomas and the higher incidence of such lesions in females 23,32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations